Online Ojek Satisfaction: Brand, Trust, and Service Quality Influence: Kepuasan Konsumen Ojek Online: Pengaruh Brand Equity, Kepercayaan, dan Kualitas Layanan - Devi Andriyanti Rosidah; Mas Oetarjo (Universitas Muhammadiyah Sidoarjo, 2022)
This descriptive study investigates the influence of brand equity, trust, and service quality on consumer satisfaction, focusing on students from a business faculty. Quantitative methods were employed, and data was collected through the distribution of questionnaires to 100 respondents. Multiple linear regression analysis was conducted using SPSS version 22 for Windows. The findings reveal significant effects of brand equity, trust, and service quality on consumer satisfaction within the context of a ride-hailing service provider. Moreover, these three variables collectively contribute to the overall consumer satisfaction experienced by customers. The implications of this research highlight the importance of cultivating brand equity, fostering trust, and delivering high-quality services to enhance consumer satisfaction in the ride-hailing industry. This study provides valuable insights for academics, practitioners, and policymakers seeking to optimize customer satisfaction and strengthen relationships with consumers. Highlights: The role of brand equity, trust, and service quality in influencing consumer satisfaction. The impact of online Ojek services on consumer satisfaction. The importance of cultivating brand equity, trust, and delivering high-quality services for enhancing consumer satisfaction in the online Ojek industry. Keywords: Brand Equity, Trust, Service Quality, Online Ojek, Consumer Satisfaction